Challenges for the Use of Local Materials in Unbound Road Subbase in Qatar - Mohamedain, Moaaz Hashim; Hassan, Khaled E.; El-Hussain, Osman; Al-Emadi, Khalid (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Current practice in Qatar is to blend local limestone with dune sand for use in unbound pavement applications. Dune sand is used to improve the properties of fine aggregate and compliance with the QCS 2014 requirements of plasticity and sand equivalent. The material has been successfully used for many years but currently facing the challenge of limited dune sand supply and recent government restrictions on its use in construction. The paper presents data on the properties of limestone obtained from different sources, tested in accordance with the QCS 2014 requirements. Variation of limestone source and the presence of clay particles greatly affected its suitability for use in unbound pavement applications. Improvement could be achieved by adjusting the grading of the material. Recommendations are made to revise the QCS 2014 specifications within the context of international specifications, when the unbound material is placed in a dry environment and away from the water level to enhance the wider utilization of local materials and sustainable construction in Qatar.